Land fictions : the commodification of land in city and country - Ghertner, D. Asher; Lake, Robert W., 1946- (Cornell series on land., 2021)
"Bringing together original research on urban, rural and peri-urban India, rapidly urbanizing China and Southeast Asia, resource expropriation in Africa and Latin America, and the neoliberal urban landscapes of North America and Europe, this book interrogates global patterns of property formation, the dispossessions property markets enact, and the popular movements to halt the growing waves of evictions and land grabs they face"